Causes of Poor Study Habits of Students as Expressed by Primary School Teachers in Nigeria - Okesina, Falilat Anike (Universitas Pendidikan Indonesia, 2019)
This research investigated the causes of poor study habits of students as expressed by primary school teachers in Nigeria. A descriptive survey design was adopted for this research, and a multi-stage sampling technique procedure was employed to draw a total sample of 200 respondents that participated in the research. The results of the research revealed that the causes of poor study habits of students consisted of poor monitoring by parents, parental educational status and laziness. Moreover, the hypothesis testing conducted in this research stated that there was a significant difference in the causes of poor study habits of students as expressed by teachers based on gender. In addition, there was no significant difference in the causes of poor study habits of students as expressed by teachers based on work experience. Based on the findings of the research, the proposed recommendation is that counselors should be employed in all schools in the country and they should be equipped with supporting facilities to prove their full support and service.